Coping strategies and health promotion through teaching-service integration in the context of the COVID-19 pandemic - Jucier Gonçalves Júnior; Sarah Cavalcante Brandão; Sandra Barreto Fernandes da Silva; Emmanuela Quental Callou de Sá (Sociedade Brasileira de Medicina de Família e Comunidade, 2020)
In the current situation related to 2019-nCoV β-coronavirus, the National Health Authorities have determined the elaboration of contingency plans (CP) that minimize the contagion and allow the functioning of essential activities. The CP presented defines a set of guidelines that allow the adequacy of the response of a public university in Northeast of Brazil linked to the Programa Mais Médicos para o Brasil. Descriptive and qualitative study, type of comment, from the analysis of the data of the CP for the definition of strategies for coping with public health emergencies. The CP consists of ten measures that include assistance via applications/social networks; monitoring of physicians who are at risk; screening of suspected/confirmed cases; production of guides/protocols; 24h psychological/technical assistance to physicians working at primary health care and provision of online courses. The methodology proposed provides different models from those trivially presented in academia and is essential to promote health education.